Pharmacological Properties of a Traditional Korean Formula Bojungchiseup-tang on 3T3-L1 Preadipocytes and High-Fat Diet-Induced Obesity Mouse Model. (29th November 2020) - Park, Yea-Jin; Seo, Dong-Wook; Gil, Tae-Young; Cominguez, Divina C.; Lee, Hwan; Lee, Dong-Sung; Han, Insik; An, Hyo-Jin
Abstract : The global obesity epidemic has nearly doubled since 1980, and this increasing prevalence is threatening public health. It has been reported that natural products could contain potential functional ingredients that may assist in preventing obesity. Bojungchiseub-tang (BJT), mentioned in the Donguibogam as an herbal medication for the treatment of edema, a symptom of obesity, consists of eleven medicinal herbs. However, the pharmacological activity of BJT has not been investigated. The present study was designed to investigate the putative effect of BJT on the adipogenesis of 3T3-L1 cells and the weight gain of high-fat diet (HFD-) fed C57BL/6 mice. Oil Red O staining was conducted to examine the amount of lipids in 3T3-L1 adipocytes. Male C57BL/6 mice were divided into three groups: standard diet group (control, CON), 45% HFD group (HFD), and HFD supplemented with 10% of BJT (BJT). The expression levels of genes and proteins related to adipogenesis in cells, WAT, and liver were analyzed by quantitative real-time polymerase chain reaction (qRT-PCR) and western blot, respectively. We found that BJT treatment significantly decreased the protein and mRNA levels of peroxisome proliferator-activated receptor γ (PPAR γ ), CCAAT/enhancer-binding protein α (C/EBP α ), and sterol regulatory element-binding protein 1 (SREBP1) in a dose-dependent manner in differentiated 3T3-L1 cells. Similar to the results of the in vitro experiment, BJT suppressed HFD-induced weight gain in an obese mouse model. In addition, BJT effectively reduced the HFD-induced epididymal adipose tissue weight/body weight index. BJT also downregulated the mRNA levels of PPARγ, C/EBPα, and SREBP1 in the epididymal adipose and liver tissue of HFD-fed obese mice. These findings suggest that BJT induces weight loss by affecting adipogenic transcription factors.